A Decade Review of Single‐Case Graph Construction in the Field of Learning Disabilities. Issue 2 (11th April 2021) - Peltier, Corey; Morano, Stephanie; Shin, Mikyung; Stevenson, Nathan; McKenna, John W.
Abstract: Single‐case research designs (SCRDs) are rigorous methods used to investigate the effects of interventions on socially important outcomes. A hallmark of SCRDs is repeated measurement of observable behavior presented in time‐series graphs. The construction of time‐series graphs can inflate Type I or Type II errors made via visual analysis. In the current investigation, we included all SCRDs published in four flagship journals in the field of learning disabilities ( Journal of Learning Disabilities, Learning Disabilities Quarterly, Learning Disabilities Research & Practice, Journal of Learning Disabilities: A Contemporary Journal ) over the last decade. A total of 47 studies including 315 graphs were included. Our findings suggest that ordinate scaling was appropriate across a majority of graphs; graphs, however, did not adhere to recommendations for x : y ratio or DPPXYR.